ESCALATING PT ZERONE INTERNATIONAL INDUSTRIES' PERFORMANCE THROUGH BUDGET PLANNING - Kuncoro, Muhammad Teguh; Ashsifa, Izza; Hidayanti, Alfiyani Nur; Mulyani, Ulva Rizky (Universitas Teknokrat Indonesia, 2023)
Planning is one of the important stages in the management process. A plan is a set of decisions about how to do something in the future. Plans are needed by both start-up companies and companies that already run for longer periods. Budget is one form or tool in planning that guides companies with financially quantitative measures. It also can help the companies evaluate their performance by comparing their budget and actual data, so the budget will be the supporting tool that will impact the company's financial position. Budget planning can be prepared by utilizing spreadsheets from Microsoft Excel. This community service program was carried out to provide: 1) education on the importance of preparing budget plans for companies, 2) assisting PT Zerone International Industries in preparing and analyzing comprehensive budget plans to improve performance and make optimal company policies, 3) help PT Zerone International Industries to determine the quantity of production, manage costs, and predict profitability. This community service program showed that the partner responded positively during the activity. This community service program allows the partner to prepare budget plans, forecast the quantity of production, costs, and profitability, and gain skills to analyze budget plans to make policies that will escalate their performance.